Early use of inhaled nedocromil sodium in children following an acute episode of asthma. Issue 4 (1st April 1999) - Edwards, A M; Lyons, J; Weinberg, E; Weinberg, F; Gillies, J D; Reid, G; Robertson, C F; Robinson, P; Dalton, M; Van Asperen, P; Wilson, C; Mullineux, J; et al.
Abstract : BACKGROUND: Current guidelines on the treatment of childhood asthma recommend the introduction of an anti-inflammatory drug in children who have persistent symptoms and require regular treatment with a bronchodilator. The efficacy and safety of inhaled nedocromil sodium (Tilade Mint aerosol) administered using a Fisonair spacer at a dose of 4 mg three times daily was compared with placebo in the treatment of asthmatic children aged 6–12 years who are symptomatic and recovering from an acute exacerbation of asthma. METHODS: A group comparative, double blind, placebo controlled trial was performed in children who were recovering from an acute episode of asthma following treatment in the emergency department of the hospital or in children referred from their general practitioner following a wheezing episode and documented evidence of at least two previous episodes of wheezing. A two week baseline period on existing bronchodilator treatment was followed by a 12 week treatment period on either nedocromil sodium (2 mg/puff) or placebo. Both treatments were administered using a Fisonair spacer at a dose of two puffs three times daily. Changes from baseline values in daytime asthma and night time asthma symptom scores, usage of rescue bronchodilators, mean peak expiratory flow (PEF) recorded twice daily on diary cards, patients' opinion of treatment, and withdrawals due to treatment failure were measured during the primary treatment period (last six weeks of treatment). RESULTS: One hundred and forty two children aged 6–12 years entered the baseline period. Sixty three were withdrawn due to failure to meet the entry criteria (18) or the criteria for asthma symptom severity (15) or reversibility (9), because they developed uncontrolled asthma (2), because they took disallowed treatment (2), or for other non-trial related reasons (17). Seventy nine patients (46 boys) of mean age 8.8 years entered the treatment period. There were significant differences in the changes from baseline values during the last six weeks of treatment in favour of nedocromil sodium compared with placebo in the primary variables of daytime asthma and night time asthma, morning and evening PEF, and the usage of rescue inhaled bronchodilators; 53% of patients reported nedocromil sodium to be very or moderately effective compared with 44% placebo. Improvement in asthma symptoms, PEF, and reduction in use of rescue bronchodilators did not reach statistical significance until after six weeks of treatment. Twenty two patients were withdrawn or dropped out during the treatment phase, 12 due to uncontrolled asthma or persistence of asthma symptoms, four due to suspected adverse drug reactions (nedocromil sodium 3 (headaches 2, angio-oedema/urticaria 1), placebo 1(persistent cough)), and six due to non-treatment related reasons. Seventy one adverse events were reported by 27 patients in the nedocromil group and 75 by 30 patients in the placebo group. CONCLUSIONS: Asthma symptoms, use of bronchodilators, and lung function can be improved significantly in children recovering from an acute exacerbation of asthma or wheeze and currently receiving treatment with bronchodilators alone by the addition of inhaled nedocromil sodium at a dose of 4 mg three times daily administered using a Fisonair holding chamber.